catena -Poly[[[diaqua[3-(pyridin-4-yl)benzoato-κ 2 O , O ′]gadolinium(III)]-bis[μ-3-(pyridin-4-yl)benzoato-κ 2 O : O ′]] monohydrate] - Li, Dong-Ying; Li, Guo-Ting (Acta crystallographica. Section E, Structure reports online, 2012)
In the title coordination polymer, {[Gd(C(12)H(8)NO(2))(3)(H(2)O)(2)]·H(2)O}(n), the Gd(III) ion is ligated by one bidentate carboxyl-ate group, four monodentate bridging carboxyl-ate O atoms and two water mol-ecules. The resulting GdO(8) polyhedron approximates to a square anti-prism. The bridging ligands link the metal ions into a [100] chain, with each pair of adjacent metal ions being bridged by two ligands. Inter-chain O-H⋯O and O-H⋯N hydrogen bonds help to establish the packing.